1999
DOI: 10.1359/jbmr.1999.14.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Femoral Neck in Hip Fracture: Cortical Bone Loss in the Inferoanterior to Superoposterior Axis

Abstract: Although bone mass is a contributory risk factor for hip fracture, its distribution about the femoral neck is also important. Femoral neck biopsies were obtained from 13 females with intracapsular hip fracture (fracture: mean age 74.3 ± 2.3 years [SEM]) and 19 cadaveric samples (control: 9 males and 10 females 79.4 ± 1.7 years) and the areas of cortical and cancellous bone were quantitated in octants. In the control group, although males had larger bones than females, the proportions of cortical and cancellous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
170
3
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(188 citation statements)
references
References 21 publications
10
170
3
5
Order By: Relevance
“…At first glance, the nearly unimpaired bone structure of the talar neck seemed contradictory given that the femoral neck has a similar weight-transmitting function and an age-related degradation of the femoral neck was reported [10,12]. Age-related cortical trabecularization and thinning were attributed to a higher risk of hip fracture in the elderly [9,10]. However, talar neck fractures have a low incidence at older age and are primarily seen in patients with a highimpact trauma [25,36].…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, the nearly unimpaired bone structure of the talar neck seemed contradictory given that the femoral neck has a similar weight-transmitting function and an age-related degradation of the femoral neck was reported [10,12]. Age-related cortical trabecularization and thinning were attributed to a higher risk of hip fracture in the elderly [9,10]. However, talar neck fractures have a low incidence at older age and are primarily seen in patients with a highimpact trauma [25,36].…”
Section: Discussionmentioning
confidence: 99%
“…Since blood vessels appear to be a significant contributor to the health and remodeling of cortical bone, it is hypothesized that the large areas of avascular calcified fibrocartilage present in the elderly femoral neck may predispose these regions to damage accumulation. The morphological properties of the cortical shell have recently been more thoroughly investigated, because of the suspected importance of the cortical shell in the susceptibility of the hip to fracture (Bell et al, 1999(Bell et al, , 2000Vajda and Bloebaum, 1999;Shea et al, 2001). Investigations into the failure mechanisms of hip fractures have observed that a localized loss of cortical bone was the dominant morphological difference between intracapsular hip fracture cases and age-matched post-mortem controls, and that the loss of cancellous bone appeared to be less significant (Bell et al, 1999(Bell et al, , 2000Crabtree et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The morphological properties of the cortical shell have recently been more thoroughly investigated, because of the suspected importance of the cortical shell in the susceptibility of the hip to fracture (Bell et al, 1999(Bell et al, , 2000Vajda and Bloebaum, 1999;Shea et al, 2001). Investigations into the failure mechanisms of hip fractures have observed that a localized loss of cortical bone was the dominant morphological difference between intracapsular hip fracture cases and age-matched post-mortem controls, and that the loss of cancellous bone appeared to be less significant (Bell et al, 1999(Bell et al, , 2000Crabtree et al, 2001). Regions of generalized cortical bone loss in the femoral neck (the superior-posterior and inferior-anterior regions) in hip fracture cases also correspond to the regions where the fractional area of calcified fibrocartilage is highest (Bell et al, 1999(Bell et al, , 2000Vajda and Bloebaum, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(23) However, there is still controversy about the respective contributions of trabecular and cortical bone compartments to hip fracture risk. Some authors have attributed the exponential increase in hip fracture risk with aging to thinning of the cortex of the neck, (24,25) whereas others suggest a synergistic action and a decline in both cortical and trabecular bone. (26)(27)(28) Mechanical testing of excised femoral necks also has given variable results, ranging from cortical contributions of 40% to 60% (14,26) to almost 100% (29) for overall femoral strength.…”
Section: Introductionmentioning
confidence: 99%